Pengaruh Konsentrasi NaOH pada Proses Deasetilasi Kitin terhadap Derajat Deasetilasi Kitosan - Herman Aldila; Atin Nuryadin; Desy Yuliana Dalimunthe (Jurusan Fisika, Universitas Bangka Belitung, 2021)
Chitosan have been successfully produced from the dried shrimp home industry waste (Bangka, Indonesia). Extraction of chitosan was carried out in four steps: deproteinization, demineralization, decolorization and deacetylation of chitin. The effect of NaOH concentration on deacetylation process was studied. The results shown that the increase of NaOH concentration from 20% to 60%, the chitosan DD increased. The diffusion rate of OH- causes increment of OH- attack to the amino group thus realizing the effective deacetylation of chitin. The highest chitosan DD was up to 69.49% is achieved under the optimized conditions of this process and the occurrence of deacetylation structurally demonstrated by the Fourier transform infrared (FTIR) characterization.